Bupivacaína, Ropivacaína e Levobupivacaína em Analgesia e Anestesia de Parto. Repercussões Materno-Fetais - Nakamura, G. [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Do Nascimento, P. [UNESP]; Rugollo, L. M S S [UNESP] (My University, 2000)
Background and Objectives - Bupivacaine has been a very useful local anesthetic in Obstetrics in spite of its potential cardiotoxicity. In obstetric analgesia, ropivacaine is preferred to bupivacaine, and levobupivacaine is less cardiotoxic than the racemic mixture. The aim of this study was to compare the maternal-fetal effects of bupivacaine, ropivacaine and levobupivacaine in obstetric analgesia and anesthesia. Methods - Participated in this study 33 term pregnant women, physical status ASA I and II submitted to epidural anesthesia who received 18.75 mg (in 15 ml completed with 9% saline) of: GI - bupivacaine, GII - ropivacaine, and GIII - levobupivacaine. Pain intensity, sensory block level, onset time, quality of analgesia, motor block intensity, analgesia duration and time for labor resolution were evaluated. For vaginal delivery, 40 mg (in 8 ml of saline) of the same local anesthetic were used; for cesarean delivery, the dose has been mg in 20 ml solution. Newborns of these mothers were evaluated through the Apgar score in minutes 1, 5 and 10, and through the Amiel-Tison method (neurologic and adaptative capacity score - NACS) at 30 min, 2 h, and 24 h. Results - There were no significant statistical differences among groups as to sensory block level, onset time, quality of analgesia, labor analgesia duration, time for labor resolution, and Apgar scores at minute 1. Ast to motor block, GIII > GII and GI was intermediary. In relation to pain intensity, there was a trend for GI > GIII. For Apgar scores in minute 5, GII > (GI = GIII), and in minute 10 (GI = GII) < GIII. NACS at 2 h showed, GII > GI > GIII, and at 24 h, GII > GIII > GI. Conclusions - Ropivacaine has relieved maternal pain with less motor block. Newborns of GII mothers (ropivacaine) showed the best Apgar and NACS scores.
Bupivacaine, ropivacaine and levobupivacaine in extradural analgesia and labor anesthesia. Maternal-fetal effects
Keywords: Analgesia: Labor; Anesthethic techniques, regional: Epidural; Anesthetics, Local: Bupivacaine, levobupicacaine, ropivacaine; bupivacaine; levobupivacaine; ropivacaine; adult; anesthesia induction; anesthesia level; anesthetic recovery; Apgar score; clinical article; drug effect; epidural anesthesia; female; human; neuromuscular blocking; obstetric analgesia; obstetric anesthesia; pain assessment